PERAN INTERMEDIASI SOSIAL PERBANKAN SYARIAH: INISIASI PELAYANAN KEUANGAN BAGI MASYARAKAT MISKIN - Muhammad Syafii Antonio; Hilman Fauzi Nugraha (Jurnal Keuangan dan Perbankan, 2012)
Syariah banking was getting criticisms because it was not able to do its reality as the Islamic value manifestationwhich could be felt by people. These criticisms at least could be related to some indicators like contractdomination of non-profit sharing (murabahah) on syariah banking practice which could only be enjoyed by upmiddle class people, or like syariah banking still did not have innovative product which could touch poorsociety. This paper discussed and explored the possibility of social intermediation role which could be done bysyariah banking more than what financial intermediation role could do to answer inconvenient news andstigma which stated that syariah banking was not pro poor people. Based on literature study and discussion,the role of social intermediation using social fund suitable with Islamic perspective namely zakat, infaq,shadaqah, wakaf, and hibah (ZISWAH) could be applied to become the product or syariah banking addedpolicy in serving poor society through some strategies. They were (1) through special enterprise unit (UUK) ofsocial intermediation and (2) cooperation through LKMS special for poor society.